A Study on the Determinants of Uterovaginal Prolapse in Tertiary Hospital, Nepal - Shah, Sunil; Shrestha, Merina; Shrewastwa, Mukesh Kumar; Upreti, Arish; Jyoti, Sabita; Sinha, Kavita; Shah, Gaurav Jung; Singh, Meeta (Journal of Nepalgunj Medical College, 2025)
Introduction: Pelvic organ prolapse is the descent of the pelvic organ from its normal position. Although few genetic and idiopathic causes have been associated with it, it most commonly follows difficult and repeated child births, making it one of the most common morbidities in developing countries like Nepal.Aims: To identify determinants of utero-vaginal prolapse (UVP) among women attending gynecologic department.Methods: A hospital-based case control study was carried out from March 2023 to March 2025 among women attending Department of Gynaecology and Obstetrics at Nepalgunj Medical College.Cases were women with utero-vaginal prolapse while controls were women free from utero-vaginal prolapse but with other gynecologic disease during the same period as of cases. Descriptive analysis along with bivariate and multivariate logistic regressions was performed in Statistical Package for Social Sciences (SPSS). Adjusted odds ratio with 95% confidence interval was used and statistical significance was considered at p ≤ 0.05.Results: Out of 226 cases, only 3(4.1%) of the cases compared to 148(65.5 %) of the controls had attended delivery at health facility. Only 8(10.8%) of cases and 8(5.3%) of the controls had ever used family planning. Only 4(5.4%) of the cases and no controls had history of hysterectomy. Only 15(20.3%) of the cases and 25(16.4%) of the controls had medical problems (history of chronic cough, had history of carrying heavy objects, hypertension, diabetes mellitus and chronic constipation) This study revealed, age ≥ 40 years (AOR = 10.49; 95%CI: 4.03, 27.35), duration of labor ≥ 24 hours (AOR = 8.32; 95%CI: 3.58, 19.33), instrumental delivery (AOR = 7.40; 95%CI: 1.21, 45.28), non- utilization of family planning (AOR = 3.14; 95%CI: 1.32, 7.47) were found to have statistical significance.Conclusion: Age ≥ 40 years, prolonged labor, instrumental delivery, non-utilization of family planning were identified as determinant factors of utero-vaginal prolapse. Thus, family planning service utilization and appropriate obstetric care are advisable.